Community Science‐Informed Local Policy: A Case Study in Pinole Creek Litter Assessment. Issue 1 (3rd March 2023) - Cowger, Win; Gomez, Itzel; Martinez‐Rubin, Norma; Moriarty, Ann; Harwell, Todd; Anich, Lisa
Abstract: California is one of the only states actively managing trash in its rivers. Several community groups in Pinole, CA, USA collaborated on a Thriving Earth Exchange community science project. Its purpose was to assess the trash in Pinole Creek and identify policy development opportunities for the community. The key scientific questions were: how much trash was in the creek at the time of the study, what types of trash were most abundant, and where should the community be most concerned about trash in the creek? The team enlisted additional community volunteers at local events. A randomized sampling design and a community science‐adapted version of The San Francisco Estuary Institute's Trash Monitoring Playbook was used to survey the trash in the creek. The Thriving Earth Team estimated there were 37 m 3 and 47, 820 pieces of total trash in the creek channel with an average concentration of 2 m 3 per km and 2, 697 pieces per km. The community gained an understanding of the scale of the problem. Plastic and single‐use trash were most abundant, and the community members expressed high concern about plastic single‐use food packaging and tobacco‐related waste. The community identified locations in the creek where trash was abundant and prioritized follow‐up study locations. Seven new recommendations were presented to the Pinole City Council. The City Council unanimously voted to further discuss ordinance‐related recommendations. And that was when community science contributed to local policy development. Plain Language Summary: A community science project was conducted in Pinole California to assess trash in Pinole Creek and propose policies for mitigation. The community surveyed trash in the creek and collected data in collaboration with a scientist. The community recommended several policies and actions to the Pinole City Council which were welcomed for advancement by the City Council. Key Points: Created a framework for conducting policy informing community science research on trash in creeks through the Thriving Earth Exchange Assessed creek trash data in collaboration with the community who led the research priorities and collected the data Used community science to inform local City Council policy